DIPOLE POLARISABILITY, OSCILLATOR STRENGTH ANDMAGNETIC SUSCEPTIBILITY OF FLUORIDE ION INFLUORIDE STRUCTURE CRYSTALS - Imtani, A. (Iraqi Journal of Science, 2025)
A variational-perturbation approach is invoked to study the effect of theenvironment potential around Fluoride ion on some important electronic properties.The dipole polarisability α, oscillator strength S(-٢) and S (-١) and magneticsusceptibility χ are theoretically estimated for Fluoride ion in different potentials.Also we calculate these electronic properties in many Fluoride structure crystalssuch as CdF٢, CaF٢, PbF٢, SrF٢ BaF٢, and LiF.